APPLICATION OF PROBLEM BASED LEARNING (PBL) MODEL TO IMPROVE LEARNER LEARNING OUTCOMES IN INTEGRATED THEMATIC LEARNING IN ELEMENTARY SCHOOL - Nur Hakiki Oktaviani; Mai Sri Lena (Autentik : Jurnal Pengembangan Pendidikan Dasar, 2022)
This research is motivated by problems in the field, when teachers do not use learning models that help students think more critically, learning is still centered on teachers, teachers do not support RPP. In general, this study aims to outline the improvement of student learning outcomes towards integrated thematic learning by using a problem based learning (PBL) model in class five of SD Negeri 11 Tanjung Alai Pasaman Regency. Class action research used research on this research and uses a quantitative and quantitative approach. Planning, implementation, observation and reflection are research procedures. Research data is taken on analysis documents, observation results, test results and non-tests. The research was conducted in the second semester of the 2021/2022 school year. Teachers and students of class V of SD Negeri 11 Tanjung Alai Pasaman Regency are the subjects of research, where there are 20 students consisting of six men and fourteen women. The results of the study illustrate a) Planning in cycle one gets an average of 86.05% (B), increased in the second disiklus, namely 94.4% (SB), b) the implementation of learning in the teacher aspect, cycle one gets an average score of 80.1% (B), increased in the second degree, namely 92.8% (SB) On the student aspect, cycle one gets an average score of 76.7% (C), an increase of 92.8% (SB), c) student learning outcomes in cycle one get an avarage of 79.30 (C), an increase of 91.76 (A). so it was concluded that the use of the PBL model made students' learning outcomes increase in thematic learning in class V of SD Negeri 11 Tanjung Alai Pasaman Regency.